US FOREIGN DIRECT INVESTMENT (FDI) AND MANUFACTURING SECTOR IN MALAYSIA - Tajul Ariffin Masron; Mohd Khairul Hisyam Hassan (Asian Academy of Management Journal, 2016)
Utilising several manufacturing sub-sectors in Malaysia, this study attempts to investigate the spillover effect of US FDI on Malaysian economy. By identifying this issue, it could help in terms of selecting future FDI-related strategies in order to magnify the positive effect of FDI inflows. Applying seemingly unrelated regression (SUR) method, this study observes that there is no guarantee that FDI inflows into various sectors within manufacturing industry will generate positive externalities.